Trends in Top Incomes and their Tax Policy Implications - Matthews, Stephen (OECD Publishing, 2011)
This paper uses data derived from tax returns to analyse trends in the share of pre-tax personal income going to top income recipients. These data provide a more reliable source of information on top incomes than household surveys and allow a perspective of almost a century. Since the early 1980s there has been a recovery in the share of top incomes, especially in the share of the top percentile group. The increase started earlier and has been greater in the US than elsewhere. Strong upward trends can also be seen in other English-speaking countries, but such trends are more muted in Continental European countries. The differences in trends between countries may reflect measurement issues to some degree. An important feature of the increased share is that it is mostly attributable to higher employment and business income, not capital income, and reflects such factors as the incentive effects of cuts in (top) marginal tax rates and the fact that the remuneration of top executives and finance professionals has become increasingly related to 'performance', particularly through the use of stock and stock options. The policy implications of these trends depend in part on income mobility; and the limited data available suggest that there is significant mobility and that its scale has decreased only slightly over time. They also depend on the likely behavioural response to increased taxation of top incomes, where the empirical literature suggests that taxable income elasticities in some countries can be large. The paper considers the pros and cons of possible reforms in the light of such evidence
Keywords: Taxation